Nilai Pendidikan Islam dalam Film Buya Hamka Vol I Sutradara Fajar Bustomi - Atiyah Faturohimah (Bandung Conference Series: Islamic Education, 2024)
Abstract. In this modern era, many people have experienced a moral decline from the values of the Quran and hadits. In fact, recently the reality of human life has changed into worldliness and radicalism between groups. This requires a solution to overcome moral problems in humans. Education that focuses on Islam to overcome the problems of humans experiencing moral decline. Islamic education efforts to instill Islamic values can be done in various ways, one of which is through learning using film media. Film media is able to transfer values more easily. One film that can be used to transfer values about Islam is the film Buya Hamka Vol I. The aim of this research is to find out what values Islamic education contains in the film Buya Hamka Vol I. This research is descriptive qualitative research with a semiotic approach. Data collection techniques use documentation techniques. Meanwhile, the data analysis technique was carried out using Roland Barthes' semiotic analysis. The primary data source used by researchers is the film Buya Hamka Vol I and secondary data in the form of books, articles, journals and other relevant writings The research results show: The values of Islamic education include the value of faith in the form of faith in Allah, the Books, the Messenger, qadha and qadhar; moral values include morals towards Allah, parents, family and friends, society; Sharia values (worship) include the mahdah worship of the morning prayer, the unseen prayer and the ghair mahdah worship including saying greetings, jihad, say laailahaillah, kissing parents' hands, seeking the approval of Allah SWT, husbands are obliged to provide for their wives and families. Abstrak. Zaman modern ini banyak manusia yang mengalami kemunduran moral dari nilai-nilai Alquran dan hadits. Faktanya akhir-akair ini realitas kehidupan manusia berubah menjadi keduniawian, radikalisme antar kelompok. Hal ini perlu adanya solusi untuk mengatasi permasalahan moral pada manusia. Pendidikan yang berfokus pada islam untuk mengatasi permasalahan manusia yang mengalami kemunduran moral. Upaya pendidikan islam untuk menanamkan nilai islam bisa dilakukan dengan berbagai cara salah satunya melalui pembelajaran menggunakan media film. Media film mampu mentransfer values lebih mudah. Salah satu film yang dapat digunakan untuk mentransfer value tentang islam adalah film Buya Hamka Vol I. Tujuan penelitian ini untuk menemukan apa saja nilai-nilai pendidikan islam yang terkandung dalam film Buya Hamka Vol I. Penelitian ini merupakan penelitian kualitatif deskriptif dengan pendekatan semiotika. Teknik pengumpulan data menggunkan teknik dokumentasi. Sedangkan teknik analisis data dilakukan menggunakan analisis semiotika Roland Barthes. Sumber data primer yang digunakan oleh penelti adalah film Buya Hamka Vol I dan data sekunder berupa buku, artikel, jurnal, dan tulisan lain yag relevan. Hasil penelitian menunjukkan: Nilai-nilai pendidikan islam antara lain nilai akidah berupa iman kepada Allah, Kitab-kitab, Rasul, qadha dan qadhar; nilai akhlak meliputi akhlak terhadap Allah, orang tua, keluarga dan sahabat, masyarakat; nilai syariah (ibadah) meliputi ibadah mahdah shalat subuh, shalat ghaib dan ibadah ghair mahdah diantaranya mengucapkan salam, jihad, mentalqinkan laailahaillah, mencium tangan orang tua, mencari ridho Allah SWT, suami wajib memberi nafkah kepada istri dan keluarga